Differences The Activity Daily Living Of Hypertensive Elderly Residing With Family And Alone (Indonesian Nursing Science Journal, 2025)
Hypertension is a condition of elevated blood pressure that often leads to complications and is known as the“silent killer” because it frequently occurs without symptoms. This chronic disease is common among the elderly and can impact their independence in performing activities of daily living. A decline in physical ability due to hypertension may cause the elderly to become dependent on others in fulfilling daily physical tasks. This study aims to analyze the differences in ADL independence among elderly individuals with hypertension who live with their families and those who live alone, to determine the influence of living arrangements on their independence levels. The research uses a descriptive comparative method with a total sampling technique. The sample includes 50 elderly individuals with hypertension living with their families and 30 elderly individuals living alone, with a total of 85 respondents. The population consists of elderly individuals with hypertension residing in Licin Village, Cimalaka Sub-district, Sumedang Regency. The results showed a significant difference in ADL independence between the two groups, with a p-value of 0.001, indicating that living arrangements affect independence. Elderly individuals who live with their families tend to experience mild dependency due to receiving assistance, while those living alone are generally more independent. The findings suggest the importance of encouraging elderly individuals who live with families to increase their physical independence. This can enhance their quality of life and reduce overdependence, supporting better aging in place.